A History of Britain : 1945 to Brexit - Black, Jeremy, 1955- (Book collections on Project MUSE., 2017)
"In 2016, Britain stunned itself and the world by voting to pull out of the European Union, leaving financial markets reeling and global politicians and citizens in shock. But was Brexit really a surprise, or are there clues in Britain's history that pointed to this moment? In A History of Britain : 1945 to the Brexit, award-winning historian Jeremy Black reexamines modern British history, considering the social changes, economic strains, and cultural and political upheavals that brought Britain to Brexit. This sweeping and engaging book traces Britain's path through the destruction left behind by World War II, Thatcherism, the threats of the IRA, the Scottish referendum, and on to the impact of waves of immigration from the European Union. Black overturns many conventional interpretations of significant historical events, provides context for current developments, and encourages the reader to question why we think the way we do about Britain's past"--Provided by publisher.